The Panel Study of Income Dynamics after Fourteen Years: An Evaluation - Becketti, Sean; Gould, William; Lillard, Lee; Welch, Finis (Journal of Labor Economics, 1988)
This article considers the representativeness of the Panel Study of Income Dynamics (PSID) over its 14-year history from 1968 to 1981 given the dynamics of entry and exit from the panel. By 1981, 40% of the original members had left the sample and were replaced by new entrants who joined either existing households or new households being formed by members of the original sample. We consider the distribution of demographic characteristics and earnings equations over time, and we compare the PSID with the Current Population Survey (CPS). By either approach we find little evidence that the PSID has become unrepresentative.